Effect of Diltiazem and Low-Dose Aspirin on Platelet Aggregation and ATP Release Induced by Paired Agonists - Zucker, Marjorie L; Budd, Susan E; Dollar, Lawrence E; Chernoff, Steven B; Altman, Raul (Thrombosis and Haemostasis, 1993)
The authors studied the effects of diltiazem, administered alone and together with low-dose aspirin, on the platelet response to paired agonists. After a baseline period, 25 healthy volunteers were given oral diltiazem for 1 week (120, 240, or 360 mg/day), and then crossed over randomly between 1 week on diltiazem plus aspirin (81 mg/day), and 1 week on aspirin (81 mg/day) alone. Platelet function was tested on 2 consecutive days in each period. Synergistic platelet aggregation and ATP release were obtained at baseline using a subthreshold concentration of arachidonic acid combined with platelet activating factor, ADP, or epinephrine. Diltiazem resulted in a significant decrease from baseline in platelet aggregation and ATP release using the arachidonic acid-epinephrine combination (35% and 40% decrease, respectively, p <0.01) and a significant decrease in aggregation using the arachidonic acid-ADP combination (22% decrease, p <0.01). The effects were neither dose-related, nor accompanied by any significant change in serum thromboxane B2 levels or bleeding times. There was no significant difference between the effects of aspirin alone and aspirin plus diltiazem on the synergistic platelet aggregation and ATP release induced by the paired agonists, or on thromboxane B2 levels or bleeding times. Diltiazem administered in vivo partially inhibits the synergistic platelet aggregation and ATP release induced by paired agonists; however, in contrast to a previous in vitro study it does not potentiate the platelet-inhibitory effect of aspirin.